1998
DOI: 10.1002/(sici)1097-4628(19980926)69:13<2533::aid-app2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Natural weathering of polypropylene films. II. Ultimate properties and exposure time

Abstract: Changes in the ultimate properties brought about by outdoor weathering during the rainy season of polypropylene (PP) films were studied. The results obtained showed that the draw ratio l d , tensile stress s b , breaking ratio l b , breaking factor (BF), work draw U d , and work for rupture U r all increased with increase in outdoor exposure time, attaining a maximum at about 240-h exposure time, before decreasing with further increases in exposure time. On the other hand, the draw ratio d s remained practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Polymer degradation is mainly caused by chemical bond scission reactions in macromolecules [3]. Several studies have been reported on the thermal, photo, biological and outdoor weathering of polymer composites [4][5][6][7][8]. It was found that long-term exposure of the composites to elevated conditions affect the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer degradation is mainly caused by chemical bond scission reactions in macromolecules [3]. Several studies have been reported on the thermal, photo, biological and outdoor weathering of polymer composites [4][5][6][7][8]. It was found that long-term exposure of the composites to elevated conditions affect the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%